Assessment of Free Drinking Water Facilities and Its Potential Health Risks: A Study in the University X - Lumbantobing, Indah Actry Zane; Wispriyono, Bambang; Kurniasari, Fitri; Fauzia, Sifa; Ayyasy, Muhammad Nur Ihsan; Haura, Alissa Siti; Labibah, Ghina; Akmal, Muhammad Abiyyu; Heryadi, Kirana Mahadewi; Alfianti, Firda; Fauziyah, Nuranida (UI Scholars Hub, 2024)
University X offers free drinking water facilities. However, it has a significant problem in accessing safe drinking water. This study aimed to examine the microbial and chemical parameters of the free drinking water facilities at University X. The microbial quality was assessed by evaluating the total coliform bacteria, and the chemical parameter assessment, substances such as nitrate, iron, manganese, hexavalent chromium, and fluoride were analyzed across 12 water samples from various locations within the university. Among these, only total coliform and fluoride levels exceeded the guidelines of the World Health Organization (WHO) and the Indonesian Ministry of Health. An Environmental Health Risk Assessment was also conducted to discern potential health hazards among the 112 respondents. This study found no potential non-carcinogenic health risks associated with consuming water from the facilities. However, a sample in one location tested positive for total coliform, and the nitrate and manganese concentrations in another location did not meet the Indonesian Ministry of Health standards. The findings suggested that the free drinking water provided by University X is safe for consumption. Nonetheless, regular maintenance of the treatment facilities is needed to ensure that water quality remains suitable and clean.